PERANCANGAN USER INTERFACE SISTEM INFORMASI E-LEARNING MENGGUNAKAN METODE DESIGN SPRINT - Helmawan, I Kadek Dwi; Paramitha, A.A. Istri Ita; Suyasa, I Putu Buda (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
This study aims to design a user interface (UI) for the e-learning information system at Universitas Primakara using the Design Sprint method, addressing the challenges posed by previous e-learning platforms, such as frequent maintenance and suboptimal user experience. The Design Sprint approach—comprising Map & Target, Sketch, Decide, Prototype, and Test—was implemented to produce a UI design that is user-centered, intuitive, and effective. Data collection involved interviews, observations, and literature studies, while usability testing was conducted using Maze and UEQ+. The resulting prototype, created in Figma, focused on the lecturer’s interface and included key features such as a simplified dashboard and responsive navigation. Maze testing of the login interface showed a 100% success rate with minimal misclicks and an average completion time of 2.9 seconds, indicating strong usability. UEQ+ results revealed a high score in Perspicuity (2.37), suggesting that users found the system easy to understand, while Stimulation scored lowest (1.47), highlighting the need for more engaging elements. The overall KPI average was 2.01 with a standard deviation of 0.76, reflecting high and consistent user satisfaction.